Proposal of a post-prostatectomy clinical target volume based on pre-operative MRI: volumetric and dosimetric comparison to the RTOG guidelines - Croke, Jennifer; Maclean, Jillian; Nyiri, Balazs; Li, Yan; Malone, Kyle; Avruch, Leonard; Kayser, Cathleen; Malone, Shawn (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Recurrence rates following radiotherapy for prostate cancer in the post-operative adjuvant or salvage setting remain substantial. Previous work from our institution demonstrated that published prostate bed CTV guidelines frequently do not cover the pre-operative MRI defined prostate. Inadequate target delineation may contribute to the high recurrence rates, but increasing target volumes may increase dose to organs at risk. Methods We propose guidelines for delineating post-prostatectomy target volumes based upon an individual’s co-registered pre-operative MRI. MRI-based CTVs and PTVs were compared to those created using the RTOG guidelines in 30 patients. Contours were analysed in terms of absolute volume, intersection volume (Jaccard Index) and the ability to meet the RADICALS and QUANTEC rectal and bladder constraints (tomotherapy IMRT plans with PTV coverage of V98% ≥98%). Results CTV MRI was a mean of 18.6% larger than CTV RTOG: CTV MRI mean 138 cc (range 72.3 - 222.2 cc), CTV RTOG mean 116.3 cc (range 62.1 - 176.6 cc), (p < 0.0001). The difference in mean PTV was only 4.6%: PTV MRI mean 386.9 cc (range 254.4 – 551.2), PTV RTOG mean 370 cc (range 232.3 - 501.6) (p = 0.05). The mean Jaccard Index representing intersection volume between CTVs was 0.72 and 0.84 for PTVs. Both criteria had a similar ability to meet rectal and bladder constraints. Rectal DVH: 77% of CTV RTOG cases passed all RADICALS criteria and 37% all QUANTEC criteria; versus 73% and 40% for CTV MRI (p = 1.0 for both). Bladder DVH; 47% of CTV RTOG cases passed all RADICALS criteria and 67% all QUANTEC criteria, versus 57% and 60% for CTV MRI (p = 0.61for RADICALS, p = 0.79 for QUANTEC). CTV MRI spares more of the lower anterior bladder wall than CTV RTOG but increases coverage of the superior lateral bladder walls. Conclusion CTV contours based upon the patient’s co-registered pre-operative MRI in the post-prostatectomy setting may improve coverage of the individual’s prostate bed without substantially increasing the PTV size or dose to bladder/ rectum compared to RTOG CTV guidelines. Further evaluation of whether the use of pre-operative MRI improves local control rates is warranted.